A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India - Majumder, Amitava; Drumont, Alain; Chandra, Kailash; Dubey, Anil Kumar (Zootaxa, 2019)
The adult male and female of a new species of longhorn beetle, Sarmydus nicobarensis sp. nov. are described from the Great Nicobar and Camorta Islands, India. Illustrations of habitus and male genitalia of the new species, as well as photographs of the holotype of S. paukstadtorum Drumont, 2011 are provided.